Optimal extent of lymph node dissection in patients with gastric cancer who underwent non-curative endoscopic submucosal dissection with a positive vertical margin. Issue 12 (December 2020) - Furukawa, Kenichiro; Kamiya, Satoshi; Sugino, Takashi; Aizawa, Daisuke; Kawabata, Takanori; Notsu, Akifumi; Hikage, Makoto; Tanizawa, Yutaka; Bando, Etsuro; Takizawa, Kohei; Ono, Hiroyuki; Terashima, Masanori
Abstract: Background: The optimal extent of lymph node dissection in patients receiving non-curative endoscopic submucosal dissection (ESD) and diagnosed with a positive vertical margin is unclear. This study attempted to identify optimal candidates for D2 lymph node dissection among these patients. Methods: This study included patients who underwent gastrectomy for primary gastric cancer following non-curative ESD with a positive vertical margin between January 2002 and December 2018. We classified the patients according to the positive vertical margin pattern into an obvious exposure group and a non-obvious exposure group. We developed a score model for predicting lymph node metastasis (LNM) using factors selected by multivariate analyses and beta regression coefficients, and the incidence of LNM was evaluated. Results: This study included 110 patients. LNM was detected in 17 patients (15%). We developed a predictive scoring system as follows: tumor size >30 mm (0, No; 1, Yes) + undifferentiated type tumor in the invasive front (0, No; 2, Yes) + depth of submucosal invasion > 1500 μm (0, No; 1, Yes) + obvious tumor exposure at the vertical margin (0, No; 1, Yes). In patients with 5 points, the incidence rates of all and group 2 LNM were as high as 60% and 40%, respectively. Conversely, in patients with fewer than 5 points, the incidence rates of all and group 2 LNM were just 11% and 5%, respectively. Conclusion: In patients with 5 points according to our score model for predicting LNM, gastrectomy with D2 lymph node dissection is recommended.